The coefficients of the Jones-Dole equation for the viscosity of solutions of potassium iodide in mixtures of water and dimethylacetamide at 35°C - Singh N.P.; Singh M.M.; Tikoo P.K. (My University, 2025)
The viscosities of solutions of KI in binary mixtures of water and dimethylacetamide at 35°C in the concentration range 0.005-0.2 mol dm-3 are reported. The data are analysed in terms of the A and B parameters of the Jones-Dole equation. The value of the B coefficient first decreases and then increases after attaining a minimum at about 0.05 mole fraction of dimethylacetamide. © 1977, CSIRO. All rights reserved.